2020
DOI: 10.3390/ijerph17103399
|View full text |Cite
|
Sign up to set email alerts
|

Can Teledentistry Improve the Monitoring of Patients during the Covid-19 Dissemination? A Descriptive Pilot Study

Abstract: The aim of this pilot study was to describe the advantages of telemedicine (TM) in dental practice during the current national emergency condition due to the Covid-19 dissemination. At

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
163
1
20

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(188 citation statements)
references
References 28 publications
4
163
1
20
Order By: Relevance
“…Studies on coronaviruses, not SARS-CoV-2, such as the SARS and MERS virus, suggest that the survival time of these pathogens on surfaces, in experimental conditions, varies from a few hours to a few days depending on the material involved, concentration, temperature and humidity. It should be emphasized that this data refers to the finding of the virus RNA and not to its isolation in vital form, and therefore not related to its real infectivity [16,25,26,[39][40][41][42]].…”
Section: Data Synthesismentioning
confidence: 98%
“…Studies on coronaviruses, not SARS-CoV-2, such as the SARS and MERS virus, suggest that the survival time of these pathogens on surfaces, in experimental conditions, varies from a few hours to a few days depending on the material involved, concentration, temperature and humidity. It should be emphasized that this data refers to the finding of the virus RNA and not to its isolation in vital form, and therefore not related to its real infectivity [16,25,26,[39][40][41][42]].…”
Section: Data Synthesismentioning
confidence: 98%
“…Concern regarding this quick spread of telemedicine is related to how long the measures in place will last past the pandemic. While the pre-pandemic adoption was not high, the telemedicine model greatly benefits both the patient and the provider from a business standpoint (e.g., [19]). Providers with better telemedicine services aim to gain a better competitive advantage, from which patients can significantly benefit [20].…”
Section: Introductionmentioning
confidence: 99%
“…With a high risk of cross-infection, nonurgent elective appointments had to be postponed, and remote consultations and online professional solutions were recommended [19,20]. Several studies demonstrated that patient-doctor remote clinical consultation could monitor patients' oral health status, improve dental knowledge and reduce costs and COVID-19 dissemination [21][22][23]. Therefore, such consultations might be a substitution for dental visits when they were unavailable.…”
Section: Discussionmentioning
confidence: 99%